Gross (domestic) output – Another government con - Barnett II, William; Block, Walter E. (REVISTA PROCESOS DE MERCADO, 2016)
The new sheriff in town is Gross (Domestic) Output, or GO. This is a measure that attempts to measure not merely investment, nor final goods, nor consumption, but the quantity and value of intermediate goods. From the vantage point of its proponents, inclusion of this statistic in national income accounts is long overdue. From the perspective of its critics, such as the present authors, it is an invalid statistic, which will create more error and misunderstanding as it is incorporated into official accounts. Keywords: Gross (Domestic) Output (GO); Gross Domestic Product (GDP); Structure of production. JEL Code: E2. Resumen: El nuevo sheriff de la ciudad es la renta (doméstica) bruta. Se trata de una variable que intenta medir no sólo la inversión, los bienes finales, y el consumo, sino la cantidad y el valor de los bienes intermedios. Desde el punto de vista de sus defensores,se debería haber incluido esta estadística en la contabilidad nacional desde hace mucho tiempo. Desde la perspectiva de sus críticos, como los autores del presente trabajo, es una estadística inválida, que creará más errores y malentendidos conforme se incorpore en las cuentas oficiales. Palabras clave: Producción (doméstica) bruta, Producto interior bruto, estructura de la producción. Clasificación JEL: E2